Relationships between recall of perceived exertion and blood lactate concentration in a judo competition - Serrano, M. A.; Salvador, A.; Gonzalez-Bono, E. G.; Sanchis, C.; Suay, F. (Perceptual and Motor Skills, 2001)
Relationships between perceived exertion and blood lactate have usually been studied in laboratory or training contexts but not in competition, the most important setting in which sports performance is evaluated. The purpose of this study was to examine the relationships between psychological and physiological indices of the physical effort in a competition setting, taking into account the duration of effort. For this, we employed two Ratings of Perceived Exertion (RPE and CR-10) and lactic acid plasma concentration as a biological marker of the effort performed. 13 male judo fighters who participated in a sports club competition provided capillary blood samples to assay lactate concentrations and indicated on scale their Recall of Perceived Exertion in the total competition and again in just the Last Fight to compare the usefulness of RPE and CR-10 in assessing discrete bouts of effort and a whole session. Analysis showed that perceived exertion or the effort made during the whole competition was positively and significantly related to maximal lactate concentration and lactate increase in competition, thus extending the validity of this scale to sports contests. The Recall of Perceived Exertion scores were not significantly correlated with the duration of effort.